2009
DOI: 10.1673/031.009.0601
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antennae in Removing Entomopathogenic Fungi from Cuticle of the Termite,Coptotermes formosanus

Abstract: Our previous research has shown that the termite, Coptotermes formosanus Shiraki (Isoptera: Rhinotermitidae), protects itself from entomopathogenic fungi by mutual grooming behavior. The termite removes and discards foreign organisms, such as fungal conidia, from the body surface of its nestmates by mutual grooming behavior. The role of the antennae in detecting the condia was examind here. Three entomopathogenic fungi were used, Beauveria brongniartii 782 (Saccardo) (Hypocreales), Paecilomyces fumosoroseus K3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 14 publications
2
49
1
1
Order By: Relevance
“…This result is consistent with an earlier report stating that the increase in the frequency of allogrooming positively impacts ant survivorship (Hughes et al 2002). Therefore, allogrooming of L. japonicus can remove fungal spores, which has been previously shown in termites (Shimizu and Yamaji 2003;Yanagawa et al 2009). We need to clarify whether self-grooming can also remove fungal spores in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with an earlier report stating that the increase in the frequency of allogrooming positively impacts ant survivorship (Hughes et al 2002). Therefore, allogrooming of L. japonicus can remove fungal spores, which has been previously shown in termites (Shimizu and Yamaji 2003;Yanagawa et al 2009). We need to clarify whether self-grooming can also remove fungal spores in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, when all termites in a group were inoculated with conidia, their behavioral activity did not change with control ( Fig. 1) (Yanagawa et al, 2009(Yanagawa et al, , 2010. This indicates that termites are good at detecting foreign organisms carried by their nestmates to the population.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we studied pathogen-prevention behaviors of the termite C. formosanus with this traditional method, and did not find any change in behavior associated with fungal inoculation (Yanagawa et al, 2009(Yanagawa et al, , 2010. However, in termites, as with other social insects, it would be rare for all of the colony members to be infected with a single pathogen at the same time, since social insects have many strategies to protect themselves from such situation (Oi and Pereira, 1993;Rosengaus et al, 1998;Cremer et al, 2007;Swanson et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have revealed that termite antennae sensitively respond to the musty odors of entomopathogenic fungi (Yanagawa et al, 2009(Yanagawa et al, , 2010. To understand the role played by chemical perception in Coptotermes formosanus behavior, we investigated whether odor from entomopathogenic fungi may be the cue that induces termite hygiene behavior.…”
Section: Introductionmentioning
confidence: 99%